A modified quick, easy, cheap, effective, rugged, and safe method for determination of by‐products originating from ozonation of chlorpyrifos and diazinon spiked in cherry tomato and perilla leaf. Issue 2 (12th November 2021) - Park, Juri; Kim, Yun‐Ji; Na, Yun‐Cheol
Abstract: In this study, sample pretreatment methods have been developed for the determination of chlorpyrifos, diazinon, and their by‐products present in cherry tomato and perilla leaf using liquid chromatography‐tandem mass spectrometry. To optimize a quick, easy, cheap, effective, rugged, and safe method, the recoveries at each step were evaluated. The steps improved the recoveries of chlorpyrifos, chlorpyrifos oxon, diazinon, diazoxon, and 2‐isopropyl‐6‐methyl‐4‐pyrimidinol up to 80% or more by removing interferents, but diethyl phosphate was almost lost during the partition procedure, and the 3, 5, 6‐trichloro‐2‐pyridinol recovery was below 65%. Therefore, the compounds were evaluated using different solvent compositions based on a quick polar pesticides method; note that 100% methanol showed acceptable extraction results. The optimized method provided method detection limits ranging from 0.03 to 1.22 ng/g and good linearities ( R 2  > 0.996). The recovery values were between 82.1 and 113.3%. The intra‐ and interday reproducibility was evaluated to be within 8.6 and 9.9%, respectively. The method was applied to determine the degradation efficiency of chlorpyrifos and diazinon and their by‐products formed during plasma treatment.